Pengaruh Kompetensi Kewirausahaan dan Digital Marketing terhadap PendapatanWirausaha Perempuan Desa Mangunharjo - Hidayah, Sunnatul; Arbarini, Mintarsih; Siswanto, Yudi (STKIP PGRI SITUBONDO, 2024)
Entrepreneurship is one of the locomotives in improving the economy in Indonesia. Entrepreneurship will be able to run smoothly if an entrepreneur has good entrepreneurial competence, because with entrepreneurial competence an entrepreneur is able to design all business processes well before starting a business to obtain income. Apart from that, the development of increasingly sophisticated technology also has an impact on entrepreneurial income because technology functions as a transaction and business promotion tool that can influence entrepreneurs to be able to compete with other entrepreneurs in obtaining increased income. Therefore, the researcher aims to conduct research to determine the influence of entrepreneurial competence and digital marketing on the income of women entrepreneurs in Mangunharjo Village. The research method used is a quantitative method using a survey method which uses questionnaire techniques which are distributed to respondents in collecting data. The sample used was 70 female entrepreneur respondents from Mangunharjo Village, with data analysis techniques using multiple linear regression analysis. The research results show that entrepreneurial competence and digital marketing have a significant effect on the income of women entrepreneurs in Mangunharjo Village. The research results also show that there are still several indicators with quite low scores, such as leadership, site design and business stability owned by respondents. Based on these results, the results of this research are expected to be able to become a reference in carrying out the necessary training for women entrepreneurs.